2015
DOI: 10.2466/09.02.pr0.116k29w3
|View full text |Cite
|
Sign up to set email alerts
|

The Multidimensional Health Locus of Control Scale: Psychometric Properties and Form Equivalence

Abstract: This study examined the psychometric equivalence of Forms A and B of the Multidimensional Health Locus of Control Scale in a sample of college students (N = 370; M = 19.5 yr.; 318 Caucasians; 281 women). Given the dearth of studies that address the issue of form equivalence directly, this study sought to ascertain whether these forms could be used interchangeably by researchers. Subscales on the two forms had fairly high correlations (range of r = .77-.81), and similar alpha and omega reliability coefficients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 57 publications
1
18
0
6
Order By: Relevance
“…This may be due to differences in age and education levels of the sample groups or in the culture and beliefs of the communities in which the samples are selected. The fact that there was a positive relationship between internal control subdimension and powerful others in this study and in some other studies (Athale et al, 2010;Kassianos, Symeou, & Loannou, 2016;Ross et al, 2015) and…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This may be due to differences in age and education levels of the sample groups or in the culture and beliefs of the communities in which the samples are selected. The fact that there was a positive relationship between internal control subdimension and powerful others in this study and in some other studies (Athale et al, 2010;Kassianos, Symeou, & Loannou, 2016;Ross et al, 2015) and…”
Section: Discussionsupporting
confidence: 81%
“…This situation arises from the eighth item in the internal control subdimension, which was interpreted in the discussion of the item statistics. The reliability of the internal control subdimension was below 0.70 (Kılıç, 2016) in all studies (Athale et al, 2010;Hashemian et al, 2014;Kuwahara et al, 2004;Moshki et al, 2007) except two studies (Ross et al, 2015;Wallston et al, 1978). The internal consistency coefficient for this study was found to be low for the internal control subdimension in sample 1 (0.66), while it was in the acceptable range for sample 2 (0.72) (Kılıç, 2016).…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…(49) The concept has also been used widely in health behavior studies, where a health-specific variation on the scale is often used (the multidimensional health locus of control scales) to examine subjects such as pregnancy risks or treatment decisions for cancer. (50)(51)(52) The concept has also been applied to safety studies involving, for example, driving, aircraft piloting, or agriculture. (53)(54)(55) And locus of control has been used in studies of natural disasters, including hurricanes, flooding, and earthquakes.…”
Section: Associated Conceptsmentioning
confidence: 99%
“…Internals tend to perceive greater self‐efficacy, and also perceive lower levels of risk . The concept has also been used widely in health behavior studies, where a health‐specific variation on the scale is often used (the multidimensional health locus of control scales) to examine subjects such as pregnancy risks or treatment decisions for cancer . The concept has also been applied to safety studies involving, for example, driving, aircraft piloting, or agriculture .…”
Section: Introductionmentioning
confidence: 99%